Prezydenckie prawybory w Platformie Obywatelskiej jako przykład politycznego show - Maguś, Wojciech (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The presidential primaries in Civic Platform in 2010 were an unprecedented event in Polish politics. They were carefully planned and skillfully carried out. The clash between Sikorski and Komorowski was attractive to the mass media, due to the increasing personalization of politics. The primaries were also attractive because this undertaking was unusual. It should also be stressed that the party that organized them demonstrated that, as a result of the professionalization of communication, it was able to reach voters over the heads of the media, at least to some extent. This is exemplified by the debate between Komorowski and Sikorski, where the media were instrumentally used as a ‘conveyor belt’ to transmit content that was entirely ‘produced’ by the party.